Use of locking plates for fixation of the greater trochanter in patients with hip replacement - Allison K. Tetreault, BA; Brian J. McGrory, MD, MS (Arthroplasty Today, 2016)
Background: Fixation of the greater trochanter with total hip replacement is challenging and associated with short- and long-term complications. Locking plate technology has been used for fixation of other bones and may be applied successfully in trochanteric fixation. The purpose of this retrospective study was to analyze the utility of the use of trochanteric locking plates in total hip arthroplasty (THA) patients. Methods: From 2004 to 2014, 32 procedures were performed to fix the greater trochanter in patients with trochanteric fracture, osteotomy, or nonunion in the setting of THA. The median age at the time of surgery was 69 years. This was a primary arthroplasty in 8 of the patients, conversion from prior hip surgery in 5, and a revision in 19. The greater trochanter was fixed with locking plate alone in 15 hips and with the addition of a single cerclage cable in 17 hips. Patients were followed clinically and radiographically until healing occurred. The median duration of radiographic follow-up was 41.6 months (range: 10-112 months). Results: Osseous union occurred in 29 (90.6%) of 32 hips. The median Harris hip score was 94 (range 54-100, standard deviation = 10.4) at latest follow-up. Complications included broken hardware in 5 (15.6%) patients, of which 3 underwent subsequent hardware removal. Two additional patients elected hardware removal due to trochanteric pain. Conclusions: Locking plate technology is a successful method of fixation of the greater trochanter in patients with THA. Postoperative trochanteric pain and reoperation for hardware-related issues remain a challenge.